Redisigning the Construction of Graving Dock Gate to Get a More Optimal Design - Suci, Indah Melati; Alamsyah; Nurcholik, Samsu Dlukha; Martinus; Alie, Muhammad Zubair Muis (Maritime Park: Journal of Maritime Technology and Society, 2025)
The graving dock gate is one part of the graving dock construction. the construction of the graving dock gate that is directly facing the sea must be able to withstand the load from the water at all times. by making modifications to the Gate construction, the design results are obtained which are quite optimal in terms of weight strength. the redesign of the graving dock Gate pt.barokah galangan perkasa cannot be separated from a problem where the previous construction design was too heavy and exceeded the required laden. Causing the graving dock gate to not be able to float when the water conditions are low. The main size of the graving dock gate pt.barokah galangan perkasa is 3 meters long, 46 meters wide, 7.32 meters high. the method used in this redesign process is to use the e application of the finite element method ANSYS apdl, while 3d modeling uses SketchUp, and AutoCAD.